Empowering Teacher Engagement in Primary Schools Through Video Intervention Program - Sucianna Ghadati Rabiha; Sasmoko Sasmoko; Yasinta Indrianti (Social Economics and Ecology International Journal (SEEIJ), 2021)
Teacher engagement basically shows that the personal and existence of a qualified teacher is positioned not only as a teacher but as an integrated whole of an educator who is professional and has an Indonesian character. This concept is in line with the mandate of the 2015-2019 RPJMN as stipulated in the Ministry of Research and Technology Strategic Plan where the government seeks to strengthen overall development by emphasizing the development of economic competitive advantages, one of which is based on quality institutions and resources. Based on the results of the trials conducted, it can be concluded that the engagement of elementary school teachers in Jakarta, Bekasi and South Tangerang can be increased through the Video Intervention Program. After empowering teachers through the Video Intervention Program, elementary school teachers in Jakarta, Bekasi and South Tangerang experienced significant engagement at α<0.05. Furthermore, through the results of the self-assessment, it was found that teacher empowerment through the Video Intervention Program will further increase teacher engagement in Jakarta, Bekasi and South Tangerang, if these teachers improve themselves in carrying out religious orders.